Scaling resource recovery and reuse (RRR) innovations in low- and middle-income countries for climate change adaptation and mitigation - Danso, G.; Cofie, Olufunke O.; Okem, Andrew Emmanuel; Drechsel, Pay (Springer, 2025)
Wastes, including biomass and wastewater, have valuable resource recovery and reuse (RRR) potential. However, previous work has paid limited attention to the climate change adaptation and mitigation potential of RRR. This chapter reviews the linkages between climate change and business models of RRR innovations in building sustainable food systems. The review demonstrates that RRR can help societies adapt to climate change mitigation strategies by providing an additional value and sustainable source of nutrients—food, water, and energy. Water reuse as a mitigation strategy has demonstrated resource recovery more than technical challenges. Engineered but simple treatment systems with great cost-effectiveness and higher change of cost recovery, if integrated into an RRR concept, can help mitigate climate change. Effective adaptive measures require nature-based solutions to treat wastewater. The International Water Management Institute (IWMI) documented innovative business models with a focus on circular economy principles and sustainable food systems and has the potential to mitigate climate change impacts. Policies on reducing GHG emissions and achieving a more circular economy with wastewater use options that can mitigate negative climate change impacts are discussed in this chapter.